Major Histocompatibility Complex (MHC) diversity and its implications for human and wildlife health and conservation – A review (2023)
It is clear that the global environment has changed and is still changing. The results of climate change, pollution, human use, and misuse of natural resources are tolling on humans and global biodiversity. The appropriate response(s) to these changes can be attributed to the efficacy of the immune system. The Major Histocompatibility Complex (MHC) has a key role in maintaining global biodiversity in the face of obvious threats. Genetic variation, especially those within MHC proteins has been known to influence the ability of individuals to cope with various pathogens. In this review, we reveal from empirical research, the diversities within the MHC in wildlife, highlight the importance of MHC to wildlife and human health, emphasize the need to conserve MHC diversity for adequate conservation, and open a discussion on whether the interplay between the MHC genes and disease resistance is a question of quantity or quality. For most jawed vertebrates, classical MHC genes are the most gene-dense and polymorphic. This polymorphism in the MHC genes can be explained by host-pathogen coevolution and provides an excellent tool for determining a population's or species' immunological fitness. Their variation is undoubtedly adaptively important, and there is strong evidence that pathogen-imposed balancing selection is the primary cause of its maintenance. Over the years, variants in the MHC have been reported as major risk factors for autoimmune and infectious diseases in humans and wildlife species of conservation concern. It has been observed that, though high diversity within the MHC proffers some protection for most natural populations, this seems not to be universal. The influence of this high diversity on the survival of natural populations should be further investigated. As the debate lingers, there is a dire need to protect the present diversity at the locus. This will definitely play a very important role in maintaining the health of both humans and animals and ensuring the conservation of biodiversity in response to the inevitable changes in our world.